Facilitating online reading comprehension in enhanced learning environment using digital annotation tools - Ruhil Amal, Azmuddin (The International Academic Forum (IAFOR), 2020)
The use of technology has now become an integral part of higher education in Malaysia because of its positive outcomes in teaching and learning. Despite its use, students are not able to fully benefit from its full potential. This study investigated the use of digital annotation tools in Interactive Reading for Academic Disciplines to facilitate reading of English for Science and Technology materials in a blended course among university students. Data were collected from 12 students enrolled in English for Technical Communication in a public university on the East Coast of Peninsular Malaysia. Data collection consisted of online annotations and focus group interviews. Analysis was descriptive and thematic, using SPSS and NVivo software, respectively. Inter-rater reliability analysis was measured using Cohen Kappa reliability analysis that yielded an almost perfect score, proving that the data were reliable. The findings revealed that digital annotation tools facilitated reading comprehension among students in an online reading environment. Annotation analyses revealed consistency in interview data when students were able to paraphrase, extend and synthesize ideas. An implication from this study suggests that training students’ regarding strategies on how to deal with annotation tasks should be mandatory. This is integral for students to achieve comprehension of English for Science and Technology materials in an online environment.